Independent and Web-Based Advice for Infertile Patients Using Fertility Consult: Pilot Study - Huppelschoten, Aleida Gerarda (JMIR Form Res, 2019)
BACKGROUND: Patient-centered care—that is, care tailored to personal wishes and needs of patients—has become increasingly important. It is especially relevant in health care areas where patients suffer from a high burden of disease, such as fertility care. At present, both diagnosis and treatment for infertile couples is provided at a single hospital. As a consequence, patients are not likely to receive optimal, independent advice regarding their fertility problems. Internet-based, independent advice could be feasible for large groups of patients because it is not limited by travel distance and overhead costs. OBJECTIVE: The aim of this study was to explore the experiences of both patients and professionals with an online platform using video consultations for patients with infertility seeking independent advice for their fertility problem. METHODS: This pilot study evaluated an online platform, Fertility Consult, where patients with infertility can get independent advice by a gynecologist through a video consultation, thus eliminating the need of meeting the doctor physically. Semistructured interviews were performed with 2 gynecologists and the chairman of the Dutch patients association. This information was used for a patients’ questionnaire about their first experiences with Fertility Consult, including questions about the level of patient-centeredness and shared decision making, using the Patient-Centered Questionnaire-Infertility (PCQ-Infertility) and the CollaboRATE questionnaire, respectively. RESULTS: Of the first 27 patients enrolled at Fertility Consult, 22 responded (82%). Most patients (82%) visited Fertility Consult for a second opinion, seeking more personal attention and independent advice. The mean level of patient-centeredness on the PCQ-Infertility questionnaire was 2.78 (SD 0.58) on a scale of 0 to 3. For the CollaboRATE questionnaire (scale 0-9), patients provided a median score of 8.0 (range 7-9) on all 3 questions about shared decision making. CONCLUSIONS: Patients were satisfied with independent, well-prepared, Web-based advice; health care professionals felt they were able to provide patients with proper advice in a manner befitting patients’ needs, without any loss of quality. Future studies should focus more on the separation of advice and treatment and on Web-based consultations compared with face-to-face consultations to ascertain the possibility of increased patient involvement in the process to improve the level of patient-centered care.